Intestine-Specific NHE3 Deletion in Adulthood Causes Microbial Dysbiosis - Xue, Jianxiang; Dominguez Rieg, Jessica A.; Thomas, Linto; White, James R.; Rieg, Timo (Frontiers in Cellular and Infection Microbiology, 2022)
In the intestine, the Na+/H+ exchanger 3 (NHE3) plays a critical role for Na+ and fluid absorption. NHE3 deficiency predisposes patients to inflammatory bowel disease (IBD). In mice, selective deletion of intestinal NHE3 causes various local and systemic pathologies due to dramatic changes in the intestinal environment, which can influence microbiota colonization. By using metagenome shotgun sequencing, we determined the effect of inducible intestinal epithelial cell-specific deletion of NHE3 (NHE3IEC-KO) in adulthood on the gut microbiome in mice. Compared with control mice, NHE3IEC-KO mice show a significantly different gut microbiome signature, with an unexpected greater diversity. At the phylum level, NHE3IEC-KO mice showed a significant expansion in Proteobacteria and a tendency for lower Firmicutes/Bacteroidetes (F/B) ratio, an indicator of dysbiosis. At the family level, NHE3IEC-KO mice showed significant expansions in Bacteroidaceae, Rikenellaceae, Tannerellaceae, Flavobacteriaceae and Erysipelotrichaceae, but had contractions in Lachnospiraceae, Prevotellaceae and Eubacteriaceae. At the species level, after removing those with lowest occurrence and abundance, we identified 23 species that were significantly expanded (several of which are established pro-inflammatory pathobionts); whereas another 23 species were found to be contracted (some of which are potential anti-inflammatory probiotics) in NHE3IEC-KO mice. These results reveal that intestinal NHE3 deletion creates an intestinal environment favoring the competitive advantage of inflammophilic over anti-inflammatory species, which is commonly featured in conventional NHE3 knockout mice and patients with IBD. In conclusion, our study emphasizes the importance of intestinal NHE3 for gut microbiota homeostasis, and provides a deeper understanding regarding interactions between NHE3, dysbiosis, and IBD.